English grammar instruction that works! : developing language skills for all learners - Rothstein, Evelyn; Rothstein, Andrew (Corwin Press, 2009)
How can teachers make grammar fun to learn really, really fun and memorable? Offering a fresh perspective for teaching English grammar, the authors present essentials on the structure of the English language, a wealth of practical strategies, and numerous examples of lively, student-centered activities for building students' skills and understanding. Appropriate for all learners, this accessible book examines what students should know about language and grammar and illustrates how to: best teach students what they need to know clarify the role of vocabulary in relationship to grammar help students enlarge their sentence-making repertoire incorporate grammar with language arts and other subject areas.